Personal accident, life and other insurances - Ivamy, Hardy E. R. (London: Butterworths, 1973)
This is the fourth and final volume in the Butterworths Insurance Library. It surveys all the remaining aspects of the law of insurance, and incorporates some of the material to be found in Welford's "Accident Insurance" (2nd ed. 1932), a work which is still of considerable relevance. The first part of this book relates to personal accident insurance; part two- life insurance; part three discusses industrial; part four is property insurance; liability insurance forms part five; part six concerns guarantee insurance, and part seven- reinsurance.
Includes bibliographical footnotes and index.
ne 8/05/2018
Loans
Keywords: Insurance law; Insurance - personal accident; Insurance - life